Analgesic Effect of Switching From Oral Opioids to a Once-a-Day Fentanyl Citrate Transdermal Patch in Patients With Lung Cancer. (November 2013) - Takakuwa, Osamu; Oguri, Tetsuya; Maeno, Ken; Yokoyama, Midori; Hijikata, Hisatoshi; Uemura, Takehiro; Ozasa, Hiroaki; Ohkubo, Hirotsugu; Miyazaki, Mikinori; Niimi, Akio
A new once-a-day fentanyl citrate transdermal patch was developed in Japan. We retrospectively investigated analgesic and adverse effects of this drug in 24 patients with lung cancer. All patients were started on this patch by switching from an oral opioid. The mean pain score before switching was 2.45 (0-5); 48 hours after switching, 15 of the 24 patients showed a decreased pain score and the mean score (2.00) was significantly lower than that before switching. Of the 16 patients who had adverse effects of oral opioids, 7 patients showed improvement in their symptoms after switching. Two patients showed adverse effects of the drug but their symptoms were mild, and no patient required dose decrease. This new transdermal patch could be a useful treatment option for cancer pain.